Compliance on Patient's Admission Protocol of Birth Center Personnel in the 5th District of Camarines Sur, Philippines - Leni Malabanan (Camarines Sur Polytechnic Colleges, 2021)
This study utilized the descriptive method of research. The researchers used the questionnaire checklist as the main data gathering tool. It was supplemented by an informal interview and records review to support the data gathered. To quantify and interpret the data, appropriate statistical tools was used such as percentage technique and weighted mean. The main goal of this research is to assess the level of compliance on patients's admission protocol of birth center personnel in the 5th District of camarines Sur, Philippines.. Results of the study showed majority of the Respondents are Single, from 21-30 years old, on a job order/contractual employment status, Roman Catholic and College graduate. Further, data shows that birth center personnel are moderately complied on the indicators under Admission but complied on the indicators under Active Labor, Fully Dilated and Effaced Stage, Postpartum and Newborn Care, And on Referral. In addition, there are some factors that greatly affect the compliance of birthing facility personnel on Admission Protocol. Three top most factors that affects the compliance of birthing facility personnel on admission protocol are financial stability of the patient, transportation resources, and the distance of the hospital from the birthing facility. And lastly, the proposed plan would help strengthen the compliance of the birthing facility personnel on admission protocol. The proposed plan was formulated taking into account the results on the compliance and factors affecting the compliance of birthing facility personnel on admission protocol.